Analisis Pembelajaran E-Learning dalam Perspektif Aliran Filsafat Pendidikan Progresivisme - Irega Gelly Gera (Lisyabab : Jurnal Studi Islam dan Sosial, 2020)
Technological advances in education gave birth to a new concept called e-learning. The birth of e-learning is in line with the viewpoint of the progressive philosophy which assumes that education should always change with the times. The problem is that every change offered by both progressiveism and e-learning, apart from bringing various conveniences, also has a negative impact on education. This study aims to analyze e-learning learning in the perspective of the progressive philosophy so that the relationship between the two will be seen and assess the suitability of the two concepts in Indonesian education today. The research method used is a qualitative method with a literature review approach using various kinds of writings on e-learning and analyzed using the theory of progressive philosophy. In conclusion, the philosophy of progressivism and e-learning are similar to one another, namely in the direction of development and change in education. E-learning is more on developing learning methods, while progressiveism includes the development of all aspects of education, both methods, materials, curriculum, and goals in keeping up with the changing times. E-learning is a product of the progressive philosophy, this is due to the progressive ideology which considers education to be dynamic in moving towards the progress of the times, while e-learning is the response of the world of education in responding to these changes. Broadly speaking, it can be seen if e-learning is viewed based on the viewpoint of the progressive philosophy as having many matches with each other. others in history, curriculum, learning methods, educators and students. Both concepts in history were both born as a renewal of conventional learning. Both concepts have a curriculum that is flexible and can be changed according to changes in society. Both concepts both have student-centered teaching methods, process-centered, not material-centered. Both concepts view teachers as monitors and facilitators and view students as the center of learning.